2016
DOI: 10.1016/j.redox.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole as a promising molecule for tumor control

Abstract: This work evaluated the antitumor effects of albendazole (ABZ) and its relationship with modulation of oxidative stress and induction of DNA damage. The present results showed that ABZ causes oxidative cleavage on calf-thymus DNA suggesting that this compound can break DNA. ABZ treatment decreased MCF-7 cell viability (EC50=44.9 for 24 h) and inhibited MCF-7 colony formation (~67.5% at 5 μM). Intracellular ROS levels increased with ABZ treatment (~123%). The antioxidant NAC is able to revert the cytotoxic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 58 publications
9
55
0
Order By: Relevance
“…For this reason, we decided to focus our studies on the antitumor effect of ABZ. A recent study in a breast cancer model (MCF-7 cells) showed that ABZ inhibited cell viability [1]. Nevertheless, it is worthwhile to note that we obtained the same results in a more aggressive model.…”
Section: Effect Of Abz and Rbz And Their Cyclodextrin Inclusion Complsupporting
confidence: 83%
See 3 more Smart Citations
“…For this reason, we decided to focus our studies on the antitumor effect of ABZ. A recent study in a breast cancer model (MCF-7 cells) showed that ABZ inhibited cell viability [1]. Nevertheless, it is worthwhile to note that we obtained the same results in a more aggressive model.…”
Section: Effect Of Abz and Rbz And Their Cyclodextrin Inclusion Complsupporting
confidence: 83%
“…Cancer is a major cause of mortality worldwide despite of the large number of treatment and prevention studies. According to the World Health Organization estimates, by 2030, the global incidence is expected to increase to 21.7 million cancer cases [1][2][3]. Currently, chemotherapy is one of the most effective strategies to avoid the proliferation of malignant tumors [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some members of benzimidazole-based anthelmintic family, such as albendazole, mebendazole and flubendazole, are being considered for repurposing in cancer therapy [12]. These drugs are widely used in animals and humans as safe and effective treatments for intestinal parasites [13][14][15], but there is also evidence of their antitumor effects in melanoma, leukemia, medulloblastoma, breast and colorectal cancers [16][17][18][19][20][21][22]. Interestingly, very little is known about the effects of these drugs in PC.…”
Section: Introductionmentioning
confidence: 99%